Data availability for health system comparisons and assessments in the WHO African Region. (20th October 2021) - Polin, K; Webb, E; Quentin, W
Abstract: Background: Describing and assessing health systems is a challenging but essential task for researchers and policy makers striving to perform cross-country comparisons and to ensure evidence-based global health policy. The European Observatory on Health Systems and Policies has developed a template for country health system reviews (HiT) to systematically describe and assess health systems. To date, the HiT template has been used for countries in Europe, Asia and North America. This study reviews to what extent data for the indicators in the HiT template are available for the 47 countries of the WHO African Region. Methods: After identifying indicators in the HiT template, we explored the databases highlighted in the HiT template, as well as additional international and regional databases, to determine data availability. We extracted the country coverage and availability of indicators over time, noting gaps in data availability. Internationally available socio-demographic, macroeconomic, and mortality and health indicators were most frequently available for all 47 countries included in the study; data on the provision of services had the lowest availability. Data on human and physical resources and service provision had the most geographic and temporal variability. Information related to health system assessment, including issues around quality of care and access, if available, were geographically and temporally limited and found only in regional surveys or national sources. Conclusions: This project provides a comprehensive overview of health system-related data availability for the African Region. Regional or country group databases with regular updates, such as those managed by OECD and Eurostat, are less common in the African region, leading to a dearth of information. More work is needed to determine the most appropriate indicators and data sources for health system comparisons and assessments in the region. Key messages: We evaluated the data availability of health system indicators in the WHO African Region using indicators from the HiT template of the European Observatory on Health Systems and Policies. Socio-demographic, macroeconomic, and mortality indicators had highest availability for all 47 countries included in the study, while data on the provision of services had the lowest availability.